The Negative Impacts of the Cultural Ban and Oppression of Human Rights on the Afghan’s Psychological Condition in Khaled Hosseini’s Novels The Kite Runner and A Thousand Splendid Suns - Ahmad Misuari Gibran; M. Amir P; Herawaty Abbas (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
These This article discusses two of Khaled Hosseini’s notable novels, namely The Kite Runner (2003) and A Thousand Splendid Suns (2007). These novels describes the story where Afghanistan is affected by the negative impacts of the long-running confilicts and the other social problems. The purpose of this article is to discuss the negative impacts of the cultural ban and the violation of human rights on the characters’ psychological condition. By applying the qualitative method and the psychoanalysis theory, this article would explain how the case of cultural ban and human rights violation affected the characters in the novels. The writer would also use several additional references to strengthen the evidences in this article. The findings of this article are related to the characters’ stresses in dealing with their respective problems in each novel. In The Kite Runner, the discussion focuses on the Hazara characters named Hassan and Sohrab, with the latter being the most-discussed one. Both are the victims of Taliban atrocities where Hassan was killed by the officials, and his son Sohrab was captured and forced to be a bacha bazi (dancing boy) by Assef, the antagonist of the novel , which reflected the negative impact of violations towards his psychological development. The next result is found in the second novel titled A Thousand Splendid Suns, which focuses on the story of Mariam. In the plot, Mariam is shown to be oppressed by both his temperamental husband Rasheed and the strict regulations of Taliban, which also at least prevented her to gain her rights and triggered her stress.